2022
DOI: 10.1002/ange.202115552
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Bulk O2 and Nonbonding Oxygen State for Reversible Anionic Redox Chemistry in P2‐Layered Cathodes

Abstract: Improving the reversibility of oxygen redox is quite significant for layered oxides cathodes in sodiumion batteries. Herein, we for the first time simultaneously tune bulk O 2 and nonbonding oxygen state for reversible oxygen redox chemistry in P2-Na 0.67 Mn 0.5 Fe 0.5 O 2 through a synergy of Li 2 TiO 3 coating and Li/Ti co-doping. O 2À is oxidized to molecular O 2 and peroxide (O 2 ) nÀ (n < 2) during charging. Molecular O 2 derived from transition metal (TM) migration is related to the superstructure orderi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Similarly, Liu et al reported a Li 2 TiO 3 coating and Li/Ti codoping modified Na 0.67 Mn 0.5 Fe 0.5 O 2 with an improved reversibility of oxygen redox. 217 The Li doping in TM layers causes the formation of a nonbonding Li-O-Na configuration, which could enhance the reversibility of the oxygen redox between oxygen ions and peroxide (O 2 ) nÀ species, while Ti doping strengthens TM-O bonds which fix lattice oxygen. Moreover, surface modification coating layer could inhibit gaseous oxygen loss and reinforce crystal structure.…”
Section: Doping-integrated Coatingmentioning
confidence: 99%
“…Similarly, Liu et al reported a Li 2 TiO 3 coating and Li/Ti codoping modified Na 0.67 Mn 0.5 Fe 0.5 O 2 with an improved reversibility of oxygen redox. 217 The Li doping in TM layers causes the formation of a nonbonding Li-O-Na configuration, which could enhance the reversibility of the oxygen redox between oxygen ions and peroxide (O 2 ) nÀ species, while Ti doping strengthens TM-O bonds which fix lattice oxygen. Moreover, surface modification coating layer could inhibit gaseous oxygen loss and reinforce crystal structure.…”
Section: Doping-integrated Coatingmentioning
confidence: 99%
“…As going from early to late transition metals or to higher valence metal states, the electronegativity is increased, which enables larger overlapping between TM d and O p states and allows more covalent interactions . In this scenario, the oxygen electron density can directly participate in charge compensation, giving rise to the so-called anionic redox chemistry. , Enabling reduction/oxidation of the oxide sublattice pushes the cathode capacity beyond the limit of TM redox potentials and leads to further improvements in both the amount of energy stored and the power delivered. Unfortunately, an uncontrolled oxidation process can lead to the formation of unbound molecular oxygen, with detrimental effects on the overall capacity and long-term stability during cycling. Several strategies are being pursued to prevent such undesired reactions, and theoretical studies can reinforce the experimental efforts to this end by enlightening the origin of anionic redox at the atomistic scale. From a general perspective, the fine-tuning of TM doping is required for the activation and control of reversible O 2– /O – reactions. Playing with atom substitution at the TM site can be a tricky task, as the electrochemical properties are very sensitive to the cation chemical nature .…”
Section: Introductionmentioning
confidence: 99%
“…Substituting TM for d 0 or alkali metals, introducing TM deficiency using cation-disordered structures as well as increasing the TM–O bond covalency are among the most investigated strategies to suppress irreversible O 2 loss. , In particular, the employment of TM-defective oxides has attracted consideration as a viable strategy to enable anionic redox and thus enhance the specific capacity of layered oxides due to the emergence of nonbonding O 2p states . However, the presence of a TM vacancy in the bulk lattice can represent a suitable site to accommodate the reactive oxygen species resulting from the uncontrolled anionic redox. , In general, the development of efficient NIB cathodes could benefit from advances and knowledge already attained for LIB analogues. The relationship between TM composition and reversible anionic redox in Li-rich layered oxides (Li 2 TMO 3 ) has been extensively reported and elucidated. By correlating the oxygen frequency shifts observed in the phonon density of states along Li 2– x TMO 3 delithiation (TM = Ru, Ni, and Mn) to the nature of the TM–O chemical bond, Shao-Horn and co-workers have unveiled that lattice dynamics can affect both ion mobility and structural stability; they clarified that these effects can be successfully restrained in highly covalent TM oxides. , The presence of Ru in such Li-rich materials seems to be a key enabler to accomplish a reversible access of oxygen redox .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation